Directions in nanotechnology - V.I. Glazko (Овощи России, 2008)
Modern directions of nanotechnologies, their value, in particular, for development of genomics were considered. Data about the non-randomness of distribution of some DNA motives in genomes testified in favour of the theory of Lima-de-Faria to interrelation between the structure-functional organization of a genetic material in nano-and microscales were presented.